A competitividade da carne suína brasileira frente aos principais exportadores mundiais (1990-2012) - Gastardelo, Tiane Alves Rocha (2016)
This work has the main objective of assess the competitiveness of pork meat exports from Brazil and its most important competitors on the international market (Germany, United States, Denmark and Canada), from 1990 to 2012. To this end, the Constant Market Share (CMS) method was used, comprising three effects: world trade; destination; and competitiveness. In order to better capture the changes in exports during the time, five sub periods were chosen, 1990/1993, 1994/1998, 1999/2002, 2003/2008 and 2009/2012. The analysis has demonstrated that United States are the most competitive country during the analyzed period, followed by Brazil. Although United States are more competitive, the growth percentage from Brazil was higher, 4,449.53%, while United States had 2,055.96% of growth. For both countries, ninety percent of this growth occurred due to increasing competitiveness. Denmark was the second country in pork meat exports in 1990, while Brazil and United States were not even among the ten larger exporters. However, Denmark presented the lowest percentage growth and the main reason was the decline of the competitiveness, not showing any positive competitiveness effect in the sub periods. Despite of been less competitive than the United States and Brazil, Germany is by now the largest exporter, with 704.45% of growth. Competitiveness was key to this growth in the complete period, but the increase in the imports of its most important importers was more relevant than in the other analyzed countries. Canada was the only country were most part of the exports growth was due to world trade growth of this product. The country also outstands because of its negative growing tendency at its main trade markets, especially the United States, which has become one of the larger players of world pig farming.